Dampak Program Corporate Social Responsibility Dalam Meningkatkan Usaha - Banati Ahadiyah Nur Ahya; Dewi Rahmi (UNISBA Press, 2024)
Abstract. One of the economic sectors that can contribute to economic development is business. Business improvement is not only done by the government but also through government agencies. PT Taspen is a public company (BUMN) that can contribute to economic development through CSR programs. Corporate Social Responsibility is the company's commitment to building a better quality of life for the surrounding community. The aim of this study was to determine the impact of CSR on business performance improvement. In this study, we use descriptive method combined with quantitative method. The data used are primary data obtained through the distribution of questionnaires to 54 respondents from PT Taspen KCU Bandung preferred partners. The analysis was performed quantitatively by scoring the respondent's response results using the Likert scale. The research results show that these 4 aspects all have an impact on the sustainability of their business activities, but the strongest impact on the partner's activities is the business management aspect, as evidenced by the counterpoint. average return is 177.2, meaning PT Taspen not only provides capital but also provides training and coaching to help partners feel the impact of PT Taspen's CSR. The company continues to improve its training and education on the marketing and legal aspects of the business. Abstrak. Salah satu bidang ekonomi yang dapat membantu Pembangunan ekonomi yaitu usaha. Peningkatan usaha tidak hanya dilakukan oleh pemerintah saja, tetapi melalui instansi pemerintah PT Taspen merupakan Bada Usaha Milik Negara (BUMN) yang dapat membantu Pembangunan ekonomi melalui Program CSR. Corporate Social Responsibility adalah komitmen suatu perusahaan untuk membangun kualitas hidup yang lebih baik bersama masyarakat sekitar. Tujuan penelitian ini untuk mengetahui dampak CSR dalam meningkatkan usahaMetode deskriptif kuantitatif digunakan dalam penelitian ini. Data yang digunakan berasal dari kuesioner yang dibagikan kepada 54 mitra binaan PT Taspen KCU Bandung. Analisis kuantitatif dilakukan dengan menggunakan skala likert untuk menilai tanggapan responden. Hasil penelitian menujukan keempat aspek tersebut berdampak pada keberlangsungan usaha mereka, namun dampak yang paling kuat terhadap usaha mitra adalah aspek pengelolaan usaha, hal ini dibuktikaan dengan hasil rata-rata skor jawaban sebesar 177,2 artinya PT Taspen tidak hanya memberikan modal tetapi juga memberikan pelatihan dan pembinaan untuk membantu mitra merasakan dampak dari CSR PT Taspen. Perusahaan lebih meningkatkan pelatihan & pembinaan pada aspek pemasaran dan legalitas usaha.